Carbon nanotube array based binary gabor zone plate lenses - Deng,S; Jwad,T; Li,C; Benton,D; Yetisen,AK; Jiang,K; Dai,Q; Butt,H (Scientific Reports, 2017)
Diffractive zone plates have a wide range of applications from focusing x-ray to extreme UV radiation. The Gabor zone plate, which suppresses the higher-order foci to a pair of conjugate foci, is an attractive alternative to the conventional Fresnel zone plate. In this work, we developed a novel type of Beynon Gabor zone plate based on perfectly absorbing carbon nanotube forest. Lensing performances of 0, 8 and 20 sector Gabor zone plates were experimentally analyzed. Numerical investigations of Beynon Gabor zone plate configurations were in agreement with the experimental results. A high-contrast focal spot having 487 times higher intensity than the average background was obtained.